LED clock / Muhammad Zulhairi Kamarulzailan & Muhammad Syafiq Sidi - Kamarulzailan, Muhammad Zulhairi; Sidi, Muhammad Syafiq (2015)
This project is rarely used to develop analog clock because the development of the clock is complicated and to reduce the size of clock so it is portable and easy to use anywhere. The objectives of the project is to design LED digital clock and to display the time reading on the LED screen .. This project also develop a microcontroller program by using the assembly programming language. This project requirement are component as Atmel microcontroller , capacitor, resistance, 74 series and 6 digit 7 segment LED. Then, experimenting the project which are construct and design of the project circuit using a suitable software to ensure the circuit gives out the desired output. Next is to construct the material as shown in the diagram, refer circuit diagram and decorate or design the LED clock circuit to be neat to be presented. The output of this project, the actual time in digital and stopwatch which can be set by the switch.